Primary Healthcare Later Life (PHILL) improving services in Bangladesh and Vietnam - Ahmed, Syed Masud; Rana, AKM Masud; Kabir, Zarina Nahar (BRAC Research and Evaluation Division (RED), 2020)
The Primary Health-Care in Later Life: Improving Service in Bangladesh and Vietnam (PHILL) project seeks to identify the effectiveness of low-cost, preventive and health promotion interventions in improving the primary health care (PHC) of people sixty and over in rural communities in Bangladesh and Vietnam. The three-year project (October 2002-September 2005) is supported by the European Commission (EC) and is being implemented under a four member partnership. Partner institutions are the Karolinska Institute (K.I) in Sweden, the Bangladesh Rural Advancement Committee (BRAC) in Bangladesh, the Health Strategy and Policy Institute (HSPI) in Vietnam and University of East Anglia (UEA) in the UK. The principal strategy of the project is to integrate existing primary health care infrastructures and promote the active participation of family and community in the health care of the elderly people. The project defines primary health care as including the first level public institutional (government health care system), community level (private and voluntary health services), and self-care at the household and individual levels.